THE EFFECT OF CORPORATE GOVERNANCE MECHANISMS ON CONSTRUCTION INDUSTRY GROWTH - Saieed Mohamed A. Abdelsalam (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The study aims to test the relationship between the tools of corporate governance (board size and board meetings) and the growth of the construction industry. This study utilized quantitative data collected from secondary sources, involving a total of eight construction institutions. The data was analyzed using the Smart-PLS technique. The results indicated that one hypothesis was accepted, showing a significant relationship between board meetings and growth. Additionally, the study found that board size had a positive and significant effect on growth. By providing both theoretical and practical implications, this research helps fill the gap identified in the literature review. Furthermore, it contributes to expanding the dimensions of the debate in the construction industry sector. The timely approach of the study can assist construction institutions in enhancing their growth and addressing existing gaps.